Perancangan Ballast Piping System Pada Kapal Ro-Ro Passanger 146 M - Ikrom Tri Mahdi; Bambang Antoko; Ekky Nur Budiyanto (Politeknik Perkapalan Negeri Surabaya, 2023)
The way ballast system works in general is to fill the ballast tank located at double bottom with seawater taken from the sea chest. The sea water is sucked up by ballast pump through main pipeline and branch pipes. In addition there is a valve that functions as opening and closing of the flow, and the overboard as a drain which is above the ship's draft. On this ship, the function of a cargo ship is changed to a passenger ship. Because there was a change in the equipment in engine room, it required a re-design of the ballast system. The design of this system follows the recommendations from BKI 2022 Volume III of the Machinery Installation Regulations. The design of the ballast system piping uses a ring main type, in the form of PID design and isometric design. The total length of pipe is 241 meters with details of 165,6 meters for the main pipe and 75,4 meters for the branch pipe. Using the type of galvanized steel material with ASTM A795 standards. The nominal diameter used of this system is based on calculations, namely 250 mm for the main pipe and 90 mm for the branch pipe.